(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This review explores the synthesis and characterization of hybrid nanocomposites designed for biosensing applications. Hybrid nanocomposites, combining distinct materials at the nanoscale, offer unique properties advantageous for biosensor development. The synthesis methods discussed include chemical vapor deposition, sol-gel techniques, and self-assembly processes, among others, highlighting their effectiveness in achieving tailored nanocomposite structures. Characterization techniques such as scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), and Fourier-transform infrared spectroscopy (FTIR) are crucial for assessing structural integrity and functional properties relevant to biosensing. The review examines the influence of nanocomposite composition, morphology, and surface properties on biosensor performance, focusing on enhanced sensitivity, selectivity, and stability. Additionally, it discusses recent advancements in integrating hybrid nanocomposites with biological recognition elements like enzymes, antibodies, and DNA strands, enhancing their specificity towards target analytes. Challenges and future prospects in the field, including scalability and biocompatibility considerations, are also addressed.